2007
DOI: 10.1007/s00439-007-0344-0
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the lipase H (LIPH) gene underlie autosomal recessive hypotrichosis

Abstract: Hereditary hypotrichosis is a rare autosomal recessive disorder characterized by sparse hair on scalp and rest of the body of affected individuals. Two forms of such hypotrichosis LAH and AH have been mapped on chromosome 18q12.1 and 3q27, respectively. Mutations in desmogelin 4 (DSG4) gene have been reported to underlie LAH. Recently, a deletion mutation in Lipase H (LIPH) gene, located at AH locus, has been identified in two ethnic groups of Russian population. In the present study, a four generation Pakista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
74
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 30 publications
3
74
0
Order By: Relevance
“…The autosomal recessive forms of hair loss disorders have been shown to result from mutations in hairless (HR, MIM 225060) Cichon et al 1998), desmoglein 4 (DSG4, MIM 607892) (Kljuic et al 2003), lipase-H (LIPH, MIM 607365) (Kazantseva et al 2006;Ali et al 2007), G-protein coupled receptor (P2RY5, MIM 609239) (Shimomura et al 2008;Pasternack et al 2008;Azeem et al 2008;Tariq et al 2009) and desmocollin-3 (DSC3, MIM 600271) ) genes. The genes for the three recently reported autosomal recessive forms of hair loss disorders (Naz et al 2010;Basit et al 2010a, b) have not been identified to date.…”
Section: Introductionmentioning
confidence: 98%
“…The autosomal recessive forms of hair loss disorders have been shown to result from mutations in hairless (HR, MIM 225060) Cichon et al 1998), desmoglein 4 (DSG4, MIM 607892) (Kljuic et al 2003), lipase-H (LIPH, MIM 607365) (Kazantseva et al 2006;Ali et al 2007), G-protein coupled receptor (P2RY5, MIM 609239) (Shimomura et al 2008;Pasternack et al 2008;Azeem et al 2008;Tariq et al 2009) and desmocollin-3 (DSC3, MIM 600271) ) genes. The genes for the three recently reported autosomal recessive forms of hair loss disorders (Naz et al 2010;Basit et al 2010a, b) have not been identified to date.…”
Section: Introductionmentioning
confidence: 98%
“…AVected adult male individuals have normal beard hair (RaWque et al 2003;Ali et al 2007). Recently three clinically similar forms of hereditary hypotrichosis LAH1, LAH2 and LAH3, segregating in autosomal recessive fashion, have been mapped on human chromosomes 18q12.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in desmoglein-4 (DSG4, MIM 607892) gene have been found to be responsible for causing LAH1 phenotype (Kljuic et al 2003;RaWq et al 2004). Kazantseva et al (2006) and Ali et al (2007) reported deletion mutations in lipase-H (LIPH, MIM 607365) gene, located at LAH2 locus. Most recently Pasternack et al (2008) and Shimomura et al (2008) reported the disruption of a G protein-coupled receptor gene, P2RY5 (MIM 609239), in three Saudi Arabian and six Pakistani families with autosomal recessive hypotrichosis simplex and autosomal recessive woolly hair, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This included congenital atrichia (MIM 203655) at 8p21 Nothen et al 1998), localized hereditary hypotrichosis (LAH, MIM 607903) at 18q12.1 (Kljuic et al 2003;Rafique et al 2003), autosomal recessive hereditary hypotrichosis (LAH2, MIM 609167) at 3q27.2 (Aslam et al 2004), LAH3 (MIM 611452) at 13q14.11-q21.32 (Wali et al 2007a) and hereditary hypotrichosis with skin vesicles (MIM 613102) at 18q21.1 ). All these five conditions congenital atrichia, LAH1, LAH2, LAH3 and hereditary hypotrichosis with skin vesicles have been reported to result from mutations in hairless (HR, MIM 225060) Cichon et al 1998), desmoglein 4 (DSG4, MIM 607892) (Kljuic et al 2003;Rafiq et al 2004), lipase-H (LIPH, MIM 607365) (Kazantseva et al 2006;Ali et al 2007), G-protein coupledreceptor (P2RY5, MIM 609239) (Pasternack et al 2008;Shimomura et al 2008;Azeem et al 2008;Tariq et al 2009) and desmocollin-3 (DSC3, MIM 600271) ) genes, respectively. An autosomal dominant form of isolated hypotrichosis simplex of the scalp has been shown to result from mutations in corneodesmosin gene (CDSN, MIM 602593) (Levy-Nissenbau et al 2003).…”
Section: Introductionmentioning
confidence: 97%